Late-preterm infants, early-term infants, and timing of elective deliveries; current status in a Korean medical center. (18th April 2019) - Ko, Hyun Sun; Jang, Yu-ri; Yun, Hanggoo; Wie, JeongHa; Choi, Sae Kyung; Park, In Yang; Shin, Jong Chul
Abstract: Objective: The aim of this study was to examine the current perinatal outcomes among infants born late-preterm and early-term compared to those born full-term and evaluate the optimal gestational age for delivery. Methods: We performed a retrospective cohort study for births occurred at Seoul St. Mary's Hospital over the past 7 years. Statistical comparison was performed using χ 2 test and multivariable logistic regression models. Results: A total of 7580 women met the study criteria. Compared to 39 weeks, delivery at late-preterm and early-term had higher risk of composite morbidity, including respiratory morbidities, intracranial hemorrhage (ICH), and admission to neonatal intensive care unit (NICU) (34 weeks adjusted odds ratio [aOR]: 132.54; 95% confidence interval (CI): 74.00–240.10; 37 weeks aOR: 2.14; 95%CI: 1.65–2.77). The risks of sepsis and necrotizing enterocolitis in deliveries before 36 weeks and the risk of feeding difficulty in deliveries before 37 weeks were significantly higher than those of 39 weeks. Neonatal morbidity at deliveries was not significantly different between 38 and 39 weeks. Conclusions: Neonatal morbidities at late-preterm births are significant and surveillance for them seems increasing. Obstetricians should recognize the risk of respiratory morbidity, ICH, and NICU admission for deliveries before 38 weeks' gestation.